CUTANEOUS MYASIS CAUSED BY AFRICAN TUMBU FLY: Cutaneous Myasis - Afzal, Lt Col Waseem; Qureshi, Muhammad Asad; Farani, Tariq M. (Pakistan Armed Forces Medical Journal, 2012)
The African tumbu fly is responsible for boil like - furuncular myiasis in both humans and animals living in central and sub Saharan Africa or people visiting those areas1. Pakistan is one of the biggest contributors of Armed Forces to the UN peace keeping missions. This has exposed our troops to diseases normally not seen in our part of the world. Medical teams visiting these areas or treating the troops returning from these areas should have a good knowledge and awareness of the diseases prevalent there. A case is reported of furuncular myiasis in a young child, sibling of Indian immigrants to Burundi-Central Africa.